Zhuanggu Guanjie herbal formula mitigates osteoarthritis via the NF-κB transduction mechanism - Guowei, Gong; Yuzhong, Zheng; Xuan, Zhou; Zhi, Dai; Juanhui, Duan; Jing, Wang; Peikui, Yang; Xiangzhi, Liu; Zhen, Wen (Frontiers in Pharmacology, 2022)
Zhuanggu Guanjie herbal formula, a famous Chinese prescription, which is commonly applied for mitigating bone-related problems, clinically. According to the China Pharmacopeia (CP, 2020), this herbal formula includes 12 raw materials, and the major components are Rehmanniae Radix (RR) and Psoraleae Fructus (PF). The anti- osteoarthritis (OA) properties of this herbal prescription are well-documented in CP (2020). However, the working mechanism of this ancient herbal formula has not been clearly elucidated. Therefore, we would like to probe the anti-OA pharmaceutical values of this ancient herbal prescription. The differentiated ATDC5 cells were employed in the following experiments. In the present study, the involvements of cytokine levels and hallmark proteins reflecting inflammatory responses in Zhuanggu Guanjie Capsule (ZGC)-induced differentiated cells were detected by RT-PCR, flow cytometer, western blot and laser confocal assays. The cytokines and inflammation-specific proteins , i.e. interleukin (IL)-6, tumor necrosis factor-α (TNF-α) and inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2) and prostaglandin synthesis E2 (PGES-2) were robustly declined after incubating with ZGC for 48 hours, and the attenuation levels were in a dose-dependent manner. Furthermore, ZGC could also block NF-κB translocation from cytosol to nucleus. On the other hand, we have used MIA-OA rats model to verify the in vivo efficacies of this herbal formula. Oral administration of ZGC could attenuate OA damage by histopathological and knee joint volume analysis. The serum matrix metalloproteinase (MMP)-13 contents in the ZGC treatment group was noticeable declined as compared to the MIA model group. The in vitro and in vivo studies have clarified the anti-OA properties of ZGC and the working mechanism involved, and this herbal formula shed light on OA treatment.